ASSOCIATION BETWEEN FIRST-TRIMESTER SERUM 25-HYDROXYVITAMIN D LEVELS AND ADVERSE MATERNAL AND PREGNANCY OUTCOMES - R. Turymbekova; I. Moldaliyev; S. Kyrykbayeva (Yassawi Journal of Health Sciences, 2026)
Vitamin D deficiency is a widespread public health problem, particularly among pregnant women, and may be associated with an increased risk of adverse pregnancy outcomes. The aim of this systematic review was to evaluate the association between first-trimester serum 25-hydroxyvitamin D [25(OH)D] levels and adverse maternal and pregnancy outcomes. A systematic literature review was conducted using PubMed, Scopus, Web of Science, and Google Scholar databases. A total of 27 studies that met the inclusion criteria were analyzed. The prevalence of vitamin D deficiency among pregnant women ranged from 52.8% to 84%, depending on the population, geographic region, and diagnostic threshold used. Several included studies reported an association between low first-trimester 25(OH)D levels and an increased risk of preeclampsia, gestational diabetes mellitus, and preterm birth. Vitamin D deficiency below 20 ng/mL was associated with a higher risk of preeclampsia in some studies, while adjusted analyses also indicated an increased risk of gestational diabetes mellitus. Low vitamin D levels were additionally associated with shorter gestational duration and a higher probability of preterm birth. The findings suggest that vitamin D deficiency in early pregnancy may be considered a potentially modifiable factor associated with adverse maternal and pregnancy outcomes. Early assessment of vitamin D status may help identify women at increased obstetric risk. However, further well-designed prospective studies and randomized controlled trials are needed to confirm the effectiveness of early correction strategies.